Flood map development by coupling satellite maps and three-dimensional drafting software: Case study of the Sarawak River Basin - Kuok, King Kuok; Liew, Zun Ziet; Chiu, Po Chan (South African Water Research Commission, 2013)
Flood maps are important for local authorities in designing mitigation plans to minimise damage and loss due to flooding. In recent years, flood events in the Sarawak River Basin, Malaysia have caused damage to property, loss of life and disruption of productive activities. Currently, the available flood map for Sarawak River Basin is generated using InfoWorks River Simulation (InfoWorks RS) and spot levels are captured using the Light Detection and Ranging (LiDAR) system. However, the high cost of this flood mapping technique has motivated the development of an advanced but low-cost flood mapping method. This study was carried out to test the feasibility of using Google Earth coupled with Autocad Civil 3D in generating flood maps. Google Earth was used to obtain the elevation data, while Autocad Civil 3D was used to plot the water level surface. Data for the maximum water level, recorded since 1960, for 12 water level stations were fed into the model for flood map generation. This research confirmed that Autocad Civil 3D coupled with Google Earth is feasible for generating an updated and accurate flood map, after comparison with 2 flood maps developed previously.